ANALYSIS OF DEFENSE HUMAN RESOURCES COMPETENCY IN FACING THE INDUSTRIAL ERA 4.0 - Sekar Angkoso, Kurniawan (Berajah Journal, 2024)
This research aims to describe the Competency Analysis of Defense Human Resources in Facing the Industrial Era 4.0. This research uses the literature analysis method (library research), which is a series of research that uses data collection methods from various library sources such as books, encyclopedias, scientific journals and documents. The research results of Industrial Revolution 4.0 are actually a combination of digital technology trends with automation technology, of course having a broad influence on various sectors/fields, including the defense sector. In relation to defense human resources, the Industrial Revolution 4.0 can provide protection for the creation of national stability, national resilience and the unitary territory of the Republic of Indonesia. Meanwhile, the presence of the Industrial Revolution 4.0 era will give rise to new (additional) problems in the field of defense human resources, especially in the threat dimension aspect which will become more complex and new threats will emerge. So in the end it is necessary to increase the operational preparedness of human resources to uphold state sovereignty, maintain territorial integrity and protect the safety of the nation. Aspects of the Pancasila ideology as the basis of the state, philosophy, outlook on life are basically to maintain the integrity and sovereignty of the Republic of Indonesia, but the rapid development of science, technology and information has changed people's behavior, the political aspects of people's aspirations have not been able to be channeled and accommodated properly, the economic aspects of KKN are still widespread, inequality and limited employment opportunities as well as socio-economic life in border areas, socio-cultural aspects of the socio-cultural conditions of society, globalization and the development of science and technology can damage the socio-cultural conditions of society. The defense and security aspect is where a country that has good defense can make its people live prosperously. Not only security forces, society must also be involved in maintaining the security of a country so that it remains stable.